Navigating Challenges and Opportunities in the Renewal of Muhammadiyah’s Educational Philosophy in the Digital Era - Anwar, Aep Saepul; Sofi`i, Imam (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
This study explores the transformation of Muhammadiyah education in response to modernization and technological advancements, emphasizing the integration of Islamic values within contemporary educational frameworks. This study uses a literature review methodology to investigate theoretical and practical viewpoints on Islamic education and how they affect the academic environment in Muhammadiyah. The findings indicate that Muhammadiyah education has evolved through integrating religious and secular sciences alongside the adoption of digital technology in the learning process. This transformation presents opportunities to enhance educational accessibility and quality through digital platforms while simultaneously encountering challenges such as resistance to technological adoption, limited digital literacy among educators, and concerns over preserving Islamic values amid modernization. The study concludes that while Muhammadiyah education demonstrates adaptability to contemporary demands, maintaining equilibrium between innovation and foundational Islamic principles remains imperative. The report suggests addressing these issues by implementing ongoing technology training for teachers, reinforcing curricula based on Islamic principles, and conducting regular assessments to ensure educational reforms align with Muhammadiyah's goals. This research contributes to contextual and adaptive Islamic education discourse, offering insights for academics, practitioners, and policymakers. It empowers policymakers to play a crucial role in strengthening Muhammadiyah's educational role in the digital era.